Modal decomposition‐based global stability analysis for reduced order modeling of 2D and 3D wake flows. (23rd October 2015) - Stankiewicz, Witold; Morzyński, Marek; Kotecki, Krzysztof; Roszak, Robert; Nowak, Michał
Summary: The method for computation of stability modes for two‐ and three‐dimensional flows is presented. The method is based on the dynamic mode decomposition of the data resulting from DNS of the flow in the regime close to stable flow (fixed‐point dynamics, small perturbations about steady flow). The proposed approach is demonstrated on the wake flows past a 2D, circular cylinder, and a sphere. The resulting modes resemble the eigenmodes computed conventionally from global stability analysis and are used in model order reduction of the flow. The designed low‐dimensional Galerkin model uses continuous mode interpolation between dynamic mode decomposition mode bases and reproduces the dynamics of Navier–Stokes equations. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The method for computation of stability modes for two‐ and three‐dimensional flows is presented. The method bases on the Dynamic Mode Decomposition of the data resulting from Direct Numerical Simulation of the flow in the regime close to steady flow. The resulting modes resemble the eigenmodes of global stability analysis and are used to design low dimensional Galerkin models of theflow.